HADIS-HADIS JIHAD DALAM PEMAHAMAN KELOMPOK JAMA’AH TABLIGH PERUMNAS KOTA CIREBON - Hartati Hartati (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2018)
The reality of days numbers on the Tabligh khuruj Jama'ah contains the meaning of "fasting" refrain from all the jewelry and pleasures of the world. Although in fact a khuruj leader does not force or impose punishment on members who are not strong enough during the ruling. This shows that Jama'ah Tabligh in Perumnas Cirebon belongs to a stream of peaceful, emotionally, not radical understanding. This is evidenced by the assertion that those who are fascinated only strong 10 days still get preoccupation preaching and getting the reward of khuruj.